Compliance of accredited hospitals in Hospital Accreditation Programme for Environmental Health and Safety Services Standard (2017 - 2019) / Muhamad Aiman Abd Jalil ... [et al.] - Abd Jalil, Muhamad Aiman; Shafie, Farah Ayuni; Abdullah, Abdul Rahim; Marikar, Kadar (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Hospital accreditation programme is one of the many accreditation programmes that is being implemented in the hospitals to improve staff performance and to give the best practices to the patients. This study was conducted to determine the staff feedback or perception towards hospital accreditation programme conducted by the Malaysian Society for Quality in Health (MSQH). It focused on the compliance of all 100 accredited hospitals for 2017-2019 in Environmental Health and Safety Standard as well as to determine the factors that may cause the hospitals not to comply with the standard. The incompliance of the hospital with the standard indicates that the hospital may not provide a safe environment towards the patients and the staff. The factors that contribute to the incompliance of hospital towards the standards can be seen from the six domains; 1) Organisation and Management, 2) Human Resources, 3) Policies and Procedures, 4) Facilities and Equipment, 5) Quality Improvement Activities and 6) Special Requirements. The findings of this study showed that most of the hospital staff or healthcare providers (95-97%) from the year 20172019 agreed that hospital accreditation programme would improve their quality of care. Furthermore, 53% of the hospitals which received Partial Compliance (PC) indicated that the hospitals need to improve their environmental and safety system so that patients and staffs would be in a safe and conducive place. Analytic Hierarchy Process (AHP) technique was used to rank the domains from the lowest contributor to highest contributor by calculating each domain Criteria Weightage (CW). The calculation of Criteria Weightage (CW) showed that the Quality Improvement Activities (QIA) had the highest value of CW with a value of 0.19 followed by Facility and Equipment (F&E) and Policies and Procedures (P&P) with value of 0.18. Human Resources (HR) and Special Requirements (SR) that shared the same CW value of 0.15 were the lowest value compared to other domains. As the study manages to rank the major factor that contributes to the incompliance, the hospital management as well as their stakeholders should prioritise to improve the factor of Quality Improvement Activities in ensuring hospital staff and patients are in a safe environment.